ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAPPELAYANAN PUBLIK DI BMKG WILAYAH LOMBOK - Ulfah, Afriyas; Kirana, Nindya (Pusdiklat BMKG, 2020)
The large number of public services in the form of requests for information and weather-climate data but the lackof media owned to accommodate suggestions and criticisms from service users is the reason for the importance ofdistributing the Community Satisfaction Survey questionnaire to get the value of the Community Satisfaction Indexas a benchmark for public services at BMKG Station West Lombok Climatology Station . Data processing iscarried out based on BMKG regulations on Community Satisfaction Survey Guidelines and validity and reliabilitytesting to evaluate the validity and consistency of questionnaires given to respondents. The results obtained fromdata processing and testing that of the 62 respondents with the main occupation of the most respondents areStudents / Students giving an average value of the Community Satisfaction Index of 3.4 and an average value ofservice expectations of 3.5 and if converted into qualifications the quality of service becomes very good. The value of the validation test shows an average value of 0.003 out of 20 questions with a significance value of 0.005, whichstates that all questions in the questionnaire are acceptable to the public. The reliability test showed the results ofα = 0.720 greater than Cronbach's alpha α = 0.60, so the results of the test that this questionnaire could be usedagain for the next survey.